Dynamics and Control of Robot Manipulators - Carricato, Marco; Idà, Edoardo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Robotic manipulators are becoming increasingly complex systems in order to meet market demands for their safer and more flexible use. Complex robotic systems are modifying the way robots are perceived and exploited in several areas. The effectiveness of these systems is challenged by new problems regarding their design, control, and planning, among others. This Special Issue explores recent advances in the dynamics and control of robot manipulators, spanning from linkages to non-conventional serial and parallel robots.